Tras un denário imitativo de Turiasu hallado en Vila Real (Portugal) - Martinez Chico, David (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
The paper shows the isolated discovery of an important Iberian denarius from northem Portugal. The coin is characterized by being covered or a fake coin of the period and presenting an imitative art from Turiasu. Several reflexions and new numismatic material about the covered denarii, imitatives, hybrids and brockages also offered.